Технология дистанционной сварки - By, Л.; Ли, Х.К.; Гао, Х.М.; Жанг, Г.Ж. (Автоматическая сварка, 2008)
In this paper a design and implementation of welding telerobotic system (HIT-WTRS) is presented, which is dedicated
to remote welding maintenance in inaccessible or hazardous environment. The system integrated three technologies,
namely laser scan vision sensing (LSVS), stereoscopic video display, and virtual environment-based plan and control.
Three control modes are emphasized in this system respectively, which are teleteaching, autonomous control and virtual
environment-based supervisory control. The laser scan vision sensor is used as autonomous welding path planner, and
is also employed to provide the welding joint profile feature point for teleteaching. The graphics environment is used
as simulation and path plan platform, and is also used as multi- viewpoint supervisory window to monitor the remote
environment when arcing. Some performance results and ways to improve the system are discussed.